National Prison Entrants’ Bloodborne Virus & Risk Behaviour Survey 2004, 2007, And 2010 - Butler, Tony; Lim, David; Callander, D. (Kirby Institute, 2011)
Prisoner populations are characterised by engagement in a range of risk behaviours, most notably injecting drug use. Consequently they are at an increased risk of exposure to blood-borne viruses such as hepatitis B, hepatitis C and HIV. Previous Australian research has shown that hepatitis C is between thirty to forty times higher among prisoners compared with the general community. Therefore, surveillance of this population to detect the presence of blood-borne pathogens and identify trends in risk behaviours is important in planning effective prevention strategies. This is the third prison entrants’ survey to have been conducted; the first was undertaken in 2004 and the second in 2007. The 2010 survey was enhanced to test for three sexually transmissible infections (STI) - chlamydia, gonorrhoea, and syphilis.